2019
DOI: 10.1057/s41295-019-00186-1
|View full text |Cite
|
Sign up to set email alerts
|

The hollowing out of monetarism: the rise of rules-based monetary policy-making in the UK and USA and problems with the paradigm change framework

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 60 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…This way, a fiscal policy discussion that used to be dominated by ‘paradigm men’ progressively saw the emergence of pivotal ‘bricoleurs’ both at the helm and within the ECB (Carstensen 2011 ). This led to the juxtaposition of ideas coming from different paradigmatic homes (Carstensen and Matthijs 2018 ; Clift 2019b ), brining gradual but meaningful ideational innovations following the logic of bricolage. Research interviews revealed that ECB’s internal politics of ideas ‘entails discursive struggles […] wherein the support of powerful backers, and packaging ideas to pass through the internal review process and secure social recognition are vitally important’ (Clift 2018 , p. 28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, a fiscal policy discussion that used to be dominated by ‘paradigm men’ progressively saw the emergence of pivotal ‘bricoleurs’ both at the helm and within the ECB (Carstensen 2011 ). This led to the juxtaposition of ideas coming from different paradigmatic homes (Carstensen and Matthijs 2018 ; Clift 2019b ), brining gradual but meaningful ideational innovations following the logic of bricolage. Research interviews revealed that ECB’s internal politics of ideas ‘entails discursive struggles […] wherein the support of powerful backers, and packaging ideas to pass through the internal review process and secure social recognition are vitally important’ (Clift 2018 , p. 28).…”
Section: Discussionmentioning
confidence: 99%
“…As a first contribution, this article questions how far a policy paradigms framework (Hall 1993 ) improves our understanding of ideational change within complex supranational institutions. This analysis builds on the insights of scholars questioning the coherence and stability of policy paradigms (Blyth 2013 ; Carstensen and Matthijs 2018 ; Clift 2019b ) and is alive to the importance of disillusionment with previous ideas to create ‘political space’ and enable ‘entrepreneurs’ to ‘champion alternatives to the ideas being questioned’ (Berman 2013 , p. 227; Hay 1996 ). This research finds that new ideas have to adjust to and combine with prior ones as a consequence of the ‘flexibility and malleability’ of policy paradigms (Clift 2019a , p. 1215).…”
Section: Introductionmentioning
confidence: 99%
“…According to Blyth (2002: 31–33), such a transformation also demands a specific kind of uncertainty where actors cannot identify their interests. Some scholars have criticized the policy paradigm literature for underreporting intraparadigm change (Carstensen and Matthijs, 2018: 439–441) and ideational consistencies across paradigms (Clift, 2020: 296, 297). Boumans (2022) recently applied the perspective to trade unions and labor market liberalization.…”
Section: Trade Unions and Alternative Work Arrangementsmentioning
confidence: 99%
“…Monetary finance, according to monetarists (Adil, Hatekar & Ghosh, 2021;Kantor, 2022), affects the economy through increasing aggregate demand. According to research (Clift, 2020) When the government borrows money to cover its budget shortfall, it drives up interest rates, discourages investment, and slows the economy.…”
Section: Monetarist Theorymentioning
confidence: 99%